Isbat Nikah sebagai Upaya Hukum untuk Mencatatkan Perkawinan Tidak Tercatat secara Legal: Analisis Putusan Pengadilan Agama Tigaraksa Nomor 192/Pdt.G/2022/PA.Tgrs - Sufiati Sufiati; Yusup Hidayat (Universitas Serambi Mekkah, 2026)
This study aims to analyze the legal consequences of unregistered marriages on the legal status of husbands, wives, and children, examine marriage validation (isbat nikah) as a legal remedy to obtain legal recognition and protection, and analyze the legal reasoning of the judges in Tigaraksa Religious Court Decision Number 192/Pdt.G/2022/PA.Tgrs. This research employs a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials consist of Law Number 1 of 1974 on Marriage as amended by Law Number 16 of 2019, the Compilation of Islamic Law, Constitutional Court Decision Number 46/PUU-VIII/2010, and Tigaraksa Religious Court Decision Number 192/Pdt.G/2022/PA.Tgrs. Secondary legal materials include books, scholarly journals, research reports, and other relevant legal literature. The collected legal materials were analyzed qualitatively using a descriptive-analytical approach. The findings reveal that unregistered marriages give rise to significant legal consequences, particularly concerning the legal certainty of marital status, maintenance rights, joint marital property, inheritance rights, and legal protection for wives and children. Children born from unregistered marriages also encounter difficulties in obtaining legal identity documents, including birth certificates and recognition of their civil relationship with their fathers. Although such marriages may be considered valid under Islamic law if all essential legal requirements and pillars of marriage have been fulfilled, the absence of official registration prevents the State from providing comprehensive legal protection. The novelty of this study lies in its analysis of the judges' legal reasoning in granting an application for isbat nikah based on the parties' remarriage and the use of a Statement of Absolute Responsibility (Surat Pernyataan Tanggung Jawab Mutlak SPTJM) as supporting administrative evidence. These considerations demonstrate a more adaptive judicial approach in ensuring legal certainty for couples who previously lacked authentic proof of their marriage. This study concludes that isbat nikah constitutes an effective legal mechanism for validating and registering previously unregistered marriages, thereby ensuring legal certainty for husbands, wives, and children and safeguarding their civil rights.